Comprehensive fruit quality assessment and identification of aroma-active compounds in green pepper (Capsicum annuum L.) - Zhang, Jing; Wang, Cheng; Wang, Junwen; Yang, Yan; Han, Kangning; Bakpa, Emily Patience; Li, Jing; Lyu, Jian; Yu, Jihua; Xie, Jianming (Frontiers in Nutrition, 2023)
The wrinkled pepper (Capsicum annuum L.) is a type of chili pepper domesticated in northwestern China, with a characteristic flavor. Fifteen wrinkled and four smooth-skinned pepper varieties were evaluated for morphology, texture, color, nutrients, capsaicinoids, and volatile compounds at the mature fruit stage. The sensory evaluation showed wrinkled pepper was superior to smooth pepper in texture, and it has a highly significant correlation (p<0.01) with cuticle thickness, maximum penetrating force, lignin content, and moisture content. Citric acid was the major organic acid in peppers, accounting for 39.10–63.55% of the total organic acids, followed by quininic acid. The average oxalic acid content of smooth peppers was 26.19% higher than that of wrinkled peppers. The pungency of wrinkled pepper fruits ranged from 1748.9 to 25529.4 SHU, which can be considered slightly to very spicy, while the four smooth varieties ranged between 866.63 and 8533.70 SHU, at slightly to moderately spicy. A total of 199 volatile compounds were detected in the 19 pepper varieties. The average volatile content of wrinkled pepper was 39.79% higher than that of smooth pepper. Twenty-nine volatile compounds, including 14 aldehydes, four alcohols, three esters, three ketones, two furans, one pyrazine, one acid, and one phenol, contributed to the fragrance of peppers and could be regarded as aroma-active compounds, with 2-isobutyl-3-methoxypyrazine being the major contributor among the 19 pepper varieties. Wrinkled pepper can be confidently distinguished from smooth pepper and is of superior quality. The current findings outlined the major texture-related characteristics of pepper as well as the main aroma-active compounds, providing valuable information for pepper quality breeding and consumer guidelines.